2020
DOI: 10.1186/s12889-020-8290-z
|View full text |Cite
|
Sign up to set email alerts
|

High urban tuberculosis case notification rates can be misleading: evidence from an urban setting in Ethiopia

Abstract: Background: Tuberculosis (TB) is a major public health problem. Its magnitude the required interventions are affected by changes in socioeconomic condition and urbanization. Ethiopia is among the thirty high burden countries with increasing effort to end TB. We aimed to describe the case notification rate (CNR) for urban tuberculosis (TB) and estimate the percentage of TB patients who are not from the catchment population. Methods: This cross-sectional study used data from TB registers from 2014/15 to 2017/18.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
1
7
1
Order By: Relevance
“…Although many countries report a higher urban load (21,22), our finding could be due to rural areas being underprivileged socioeconomically and in terms of sanitary and health services provided. Alternatively, urban reporting could be over-estimated in some countries, as they report cases by site of notification center rather than by patient residence (23). Regarding the clinical presentation, it was observed that extra-pulmonary TB (EPTB) was more (59.2%) than PTB in this single-center in the ten years from 2009-2018.…”
Section: Discussionmentioning
confidence: 91%
“…Although many countries report a higher urban load (21,22), our finding could be due to rural areas being underprivileged socioeconomically and in terms of sanitary and health services provided. Alternatively, urban reporting could be over-estimated in some countries, as they report cases by site of notification center rather than by patient residence (23). Regarding the clinical presentation, it was observed that extra-pulmonary TB (EPTB) was more (59.2%) than PTB in this single-center in the ten years from 2009-2018.…”
Section: Discussionmentioning
confidence: 91%
“…Second, a modeling study in Taiwan showed that immune senescence played an important role in the age disparity between children and elders, which means patients with latent TB infection have an increased risk of developing TB as they age due to a weakening immune system with older age ( 38 ). Third, TB is a disease whose transmission is favored by the density of urban populations ( 39 ). Taiwan has seen rapid growth in living standards and nationwide coverage of high-quality, publicly funded healthcare services ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…An overview of the statistics in 30 countries with a high TB burden reveals that developing countries might need greater attention. Over 90% of the TB cases and TB-induced deaths occur in developing countries [1,6] probably because poverty plays a major role [7,8]. An estimated 60 billion USD is needed for implementing Stop TB interventions, and the total expenditure needed was 10.1 billion USD for low-to middle-income countries in 2019. available [1].…”
Section: Introductionmentioning
confidence: 99%